Advances in the development of tubular structures using extrusion-based 3D cell-printing technology for vascular tissue regenerative applications - Gi Hoon Yang; Donggu Kang; SangHyun An; Jeong Yeop Ryu; KyoungHo Lee; Jun Sik Kim; Moon-Yong Song; Young-Sik Kim; Sang-Mo Kwon; Won-Kyo Jung; Woonhyeok Jeong; Hojun Jeon (Biomaterials Research, 2022)
Abstract Until recent, there are no ideal small diameter vascular grafts available on the market. Most of the commercialized vascular grafts are used for medium to large-sized blood vessels. As a solution, vascular tissue engineering has been introduced and shown promising outcomes. Despite these optimistic results, there are limitations to commercialization. This review will cover the need for extrusion-based 3D cell-printing technique capable of mimicking the natural structure of the blood vessel. First, we will highlight the physiological structure of the blood vessel as well as the requirements for an ideal vascular graft. Then, the essential factors of 3D cell-printing including bioink, and cell-printing system will be discussed. Afterwards, we will mention their applications in the fabrication of tissue engineered vascular grafts. Finally, conclusions and future perspectives will be discussed.